Determinan Defisit Anggaran di Indonesia Tahun 1998-2021 - Dita Lusiana; Daryono Soebagiyo (Peneliti.net, 2023)
A budget deficit is a budget with state spending greater than state revenue, in which routine revenue and development revenue are insufficient to finance government spending. This study aims to analyze the effect of the exchange rate, foreign debt, SBI interest rates and inflation both simultaneously and partially on the budget deficit in Indonesia during the 1998-2021 period. This research uses secondary data in the form of time series data for the period 1998-2021 in Indonesia. The analytical method used is Ordinary Least Square (OLS). The results of the study found that the independent variable that had an influence on the Budget Deficit in Indonesia in 1998-2021 was Foreign Debt. Meanwhile, inflation, SBI interest rates and exchange rates have no effect on the budget deficit.